Features of organizing physical education for students in the conditions of distance learning - Lutsenko, Iryna; Horpynych, Oleksii; Hloba, Tetiana; Nesterenko, Oleksandr; Chykolba, Hennadii (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
Over the past few years, the conditions under which Ukraine’s development is taking place have been characterized by a number of changes and transformations. Undoubtedly, they were reflected in all social relations, including educational ones. Thus, as a result of the COVID-19 pandemic, as well as a full-scale war, from February 24, 2022, the educational process was organized in a distance format, which remains relevant to this day. At the same time, the correct selection of methods for teaching practical disciplines, such as physical education, which requires the student to use special tools and skills, is especially important. The aim of this study was to analyse qualitative approaches, on the basis of which it is possible to carry out professional training of students, including physical education, in current educational conditions. For this, the method of analysis and synthesis, comparison, deduction was used in the work. As a result, it was possible to reveal the main advantages and disadvantages of distance learning, namely the organization of physical education during it. In addition, priority tools were described, which were most often used by teachers during training sessions. It was also possible to analyse both positive and negative factors, which most affect the quality and dynamics of the educational process. It was important to form quality recommendations, related to increasing the effectiveness of teaching physical education in distance learning conditions. The practical value of the work is revealed in the fact that it can be used by educational workers during preparation for educational classes, as well as by students for independent work.